Right Coronary Artery Pseudoaneurysm With Hemopericardium: A Rare Complication of Percutaneous Coronary Intervention - Byrnes, Sean (Cureus, 2020)
While percutaneous coronary intervention (PCI) is a commonly performed procedure, it still has many serious complications. Coronary artery pseudoaneurysms can form after PCI and can progress to cardiac tamponade. We report the case of an 80-year-old male who presented for an inferior wall ST elevation myocardial infarction, had drug-eluting stents placed to the right coronary artery (RCA), and subsequently suffered a RCA pseudoaneurysm with hemopericardium. He eventually underwent pseudoaneurysm repair with off pump coronary artery bypass graft. There is no established treatment protocol, and involvement of a multidisciplinary team improves outcomes.